Construction of a novel vaccine by conjugating a B-cell epitope of DPP4 to peptide IA2(5)-P2-1 to significantly control type 1 diabetes in NOD mice. Issue 51 (18th December 2017) - Li, Ya; Cao, Huimin; Li, Yiping; Li, Zhixin; Wei, Xiaomin; Jiao, Rui; Cheng, Peng; Liu, Xiaoran; Ma, Yanjie; Xing, Yun; Tang, Jiali; Wang, Min; et al.
Highlights: A multi-epitope peptide vaccine based on DPP4 is constructed for type 1 diabetes treatment. The mechanism relies on inhibition of DPP4 activity and immune rebalance's reestablishment. The novel vaccine significantly control type 1 diabetes in NOD mice. Abstract: Type 1 diabetes is a chronic organ-specific autoimmune disease in which selective destruction of insulin-producing β cells leads to impaired glucose metabolism and its attendant complications. IA2(5)P2-1, a potent immunogenic carrier which designed by our laboratory, can induce high titer specific antibodies when carry a B cell epitope, such as B cell epitopes of DPP4, xanthine oxidase, and Urate transporter protein. In this report, we describe a novel multi-epitope vaccine composing a peptide of DPP4, an anti-diabetic B epitope of Insulinoma antigen-2(IA-2) and a Th2 epitope (P2:IPALDSLTPANED) of P277 peptide in human heat shock protein 60 (HSP60). Immunization with the multi-epitope vaccine in non-obese diabetic (NOD) mice successfully induced specific anti-DPP4 antibody, inhibited plasma DPP4 activity, and increased serum GLP-1 level. Moreover, this antibody titer was correlated with the dose of immunization (20μg, 100μg). Inoculation of this vaccine in NOD mice significantly control blood glucose level, improved glucose excursion and increased insulin level in vivo. Consistent with a lower diabetic and insulitis incidence, a induced splenic T cells proliferation and tolerance were observed. IFN-γ secretion reduced and IL-10 increased significantly in the D41-IA2(5)-P2-1 treated mice compared to P277 and control group due to the potential immunomodulatory effect of the epitope in the vaccine. Immunohistochemical analysis and cytometry showed a rebalance of Th1/Th2 in NOD mice. Our results demonstrate that this multi-epitope vaccine may serve as a promising therapeutic approach for type 1 diabetes.